Tipologi Batang Tubuh Pisau Tumbuk Lada: Sebuah Analisis Makna pada Pusaka Melayu - Amelia, Pidia; Lukitaningsih, Lukitaningsih; Purnamasari, Ika (Warisan: Journal of History and Cultural Heritage, 2023)
This article discusses the meaning contained in the body of a Malay heritage weapon called the "Pisau Tumbuk Lada". In the past, pisau tumbuk lada were weapons that were very close to the lives of Malay people. Because it not only functions as a marker of social status, but also as a component of customs, traditions, religion, and completeness of daily life. Therefore, this weapon was used by everyone from kings, nobles, traditional leaders to ordinary people. The pisau tumbuk lada is also considered a symbol of the glory of the pepper trade in the Malay world which existed in the 15th – 20th century AD. The body of the pisau tumbuk lada consists of the upstream, karah, blade, and sheath. Each part of the body has a special meaning related to aesthetic, functional, and philosophical aspects. The manufacturing materials and decorative motifs contained therein also have great philosophical values.